Integrating manufacturing systems using ISO 10303 (STEP): An overview of UNINOVA projects. (29th October 2004) - Jardim-Goncalves, Ricardo; Sousa, Pedro C.; Pimentao, Joao B.; Steiger-Garcao, Adolfo
This paper presents an historical review of the tools developed and the experience acquired by UNINOVA, the Institute for the Development of New Technologies, during the last eight years, integrating manufacturing systems using ISO 10303-STEP, in the scope of international industrial projects. The integration of commercial applications and standards has been one of the principal concerns of the work done. To promote open and scaleable solutions towards an advanced product data management supporting product life-cycle activities, a general architecture and a toolkit able to handle the standard and aid the integration tasks, was designed, developed and improved throughout those years by UNINOVA, and this provides the required mechanisms. The scope of the case studies presented here covers the furniture and road construction industries through four European projects: CIMTOFI, RoadRobot, funStep and ECOS, where the integration of the company's internal (manufacturing) and external (business) aspects are considered. The global information system architecture based on standard models is presented, as well the implementation aspects of the developments for industry. The steps followed to integrate the systems, and the results obtained in these manufacturing environments are also described and commented on.